Peran Akademisi Dalam Pemberdayaan Masyarakat Berbasis Kewirausahaan - Solichah, Solichah; Merita, Rona; Fitrotus S, Dewi (Universitas Pangeran Diponegoro Nganjuk, 2022)
One of the tridharma of higher education is community service, this is one of the social responsibilities of academics. Generally service is manifested in the form of community empowerment. Concrete manifestations of the role of academics in community empowerment include being an idea contributor, a facilitator or community assistant, and an